2001
DOI: 10.1007/s004640000255
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy reduces unnecessary appendicectomies and improves diagnosis in fertile women

Abstract: Laparoscopy reduces unnecessary appendectomies and improves diagnosis in fertile women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
62
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 8 publications
6
62
0
5
Order By: Relevance
“…As expected, a gynecologic disorder was most commonly diagnosed in this group of patients except in one who had Meckel's diverticulites. This finding is consistent with study of Larsson et al (11). They reported that a gynecologic diagnosis was found in 73% after laparoscopy, as compared with 17% after open surgery among the fertile women with a healty appendix and explained this difference by the more complete vision of the deep pelvis by laparoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, a gynecologic disorder was most commonly diagnosed in this group of patients except in one who had Meckel's diverticulites. This finding is consistent with study of Larsson et al (11). They reported that a gynecologic diagnosis was found in 73% after laparoscopy, as compared with 17% after open surgery among the fertile women with a healty appendix and explained this difference by the more complete vision of the deep pelvis by laparoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…During laparoscopy, was appendicitis misdiagnosed in only 7% of the women, from whom the appendix unnecessarily removed, whereas 34% in the open surgery group had a healthy appendix removed. 12 Ultrasonogram findings supportive of the diagnosis of appendicitis include. a peristaltic, no compressible, dilated appendix (>6 mm outer diameter)…”
mentioning
confidence: 98%
“…6 The association between the elevated SB levels and the variety of infectious diseases has been noted in few studies. [7][8][9][10][11][12][13][14][15] Some bacteria including E. Coli have been associated with increased levels of total serum bilirubin levels. 16 Amongst the patients diagnosed with Acute appendicitis pre-operatively (n=70), 47 patients (47%) were found to have increased bilirubin (>1.2 mg/dL) while 53 patients (53%) has normal bilirubin levels (≤1.2 mg/dL).…”
Section: Discussionmentioning
confidence: 99%